Distractions in the cardiac catheterisation laboratory: impact for cardiologists and patient safety. Issue 2 (2nd December 2020) - Mahadevan, Kalaivani; Cowan, Elena; Kalsi, Navneet; Bolam, Helena; Arnett, Richard; Hobson, Alex; Guha, Kaushik; Morton, Geraint; Brennan, Peter A; Kalra, Paul R
Abstract : Objective: To understand human factors (HF) contributing to disturbances during invasive cardiac procedures, including frequency and nature of distractions, and assessment of operator workload. Methods: Single centre prospective observational evaluation of 194 cardiac procedures in three adult cardiac catheterisation laboratories over 6 weeks. A proforma including frequency, nature, magnitude and level of procedural risk at the time of each distraction/interruption was completed for each case. The primary operator completed a National Aeronautical and Space Administration (NASA) task load questionnaire rating mental/physical effort, level of frustration, time-urgency, and overall effort and performance. Results: 264 distractions occurred in 106 (55%) out of 194 procedures observed; 80% were not relevant to the case being undertaken; 14% were urgent including discussions of potential ST-elevation myocardial infarction requiring emergency angioplasty. In procedures where distractions were observed, frequency per case ranged from 1 to 16 (mean 2.5, SD ±2.2); 43 were documented during high-risk stages of the procedure. Operator rating of NASA task load parameters demonstrated higher levels of mental and physical workload and effort during cases in which distractions occurred. Conclusions: In this first description of HF in adult cardiac catheter laboratories, we found that fewer than half of all procedures were completed without interruption/distraction. The majority were unnecessary and without relation to the case or list. We propose the introduction of a 'sterile cockpit' environment within catheter laboratories, as adapted from aviation and used in surgical operating theatres, to minimise non-emergent interruptions and disturbances, to improve operator conditions and overall patient safety.